2020
DOI: 10.4018/978-1-7998-3729-9.ch013
|View full text |Cite
|
Sign up to set email alerts
|

Dancing With the Dreamweavers

Abstract: This chapter revolves around the impact of socio-political diaspora to the concept of tribal-ancestral land, which is sacred to the community and the cultural identity of the T'boli, an ethno-linguistic group. A narrative discourse approach is used to illustrate the tribe's struggles to the existing hegemony, particularly with the dynamics between the tribe and other inhabitants, the intrusions of other values and exploitations of their ancestral domains as explored across a changing sociocultural milieu. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…When chemistry is approached through ionic liquids, it illustrates what kind of chemistry is needed, e.g., in the textile industry. This viewpoint may also broaden the view of the connection between chemistry innovation and society [16]. In the best-case scenario, through contextbased teaching on ionic liquids, it is possible to support relevance both in the individual and societal dimensions, and to increase understanding of the meaning of chemistry and its connection to society now and in the future.…”
Section: Design Solution 1: Supporting the Relevance Via Practical Wo...mentioning
confidence: 98%
See 4 more Smart Citations
“…When chemistry is approached through ionic liquids, it illustrates what kind of chemistry is needed, e.g., in the textile industry. This viewpoint may also broaden the view of the connection between chemistry innovation and society [16]. In the best-case scenario, through contextbased teaching on ionic liquids, it is possible to support relevance both in the individual and societal dimensions, and to increase understanding of the meaning of chemistry and its connection to society now and in the future.…”
Section: Design Solution 1: Supporting the Relevance Via Practical Wo...mentioning
confidence: 98%
“…Therefore, more research is needed in order to evaluate the comprehensive sustainability of using ionic liquids as solvents [40,41]. Ionic liquids are a topical example of innovation of green chemistry, made possible by science and technology [16]. Hernani et al [16] also suggested that the context includes many opportunities for teaching about chemistry subject matter and for developing thinking skills.…”
Section: Theoretical Problem Analysis: the Possibilities Of The Ionic...mentioning
confidence: 99%
See 3 more Smart Citations